Study on Seismic Performance of Connecting Prefabricated Coupling Beam and Shear Wall with Equivalent Bars - Bo Zheng; Ming Li; Xuyi Liu; Zhen Wang; Chunyan Wang (Advances in Civil Engineering)
This study proposes a new type of method for the connection of the prefabricated coupling beam and shear wall to solve the problems in the construction of assembled frame-shear wall structures. To investigate the seismic properties of this new type of assembled coupling beam, experiments with 2 groups of test pieces under low-period cycling loads were completed. Furthermore, this study studied some important influence factors. Results show that this novel coupling beam has a similar performance to the cast-in-place coupling beam. The bearing capacity and energy dissipation capacity of cast-in-place structures increase with the increase in end block thickness and the ductility inversely, yet the bearing capacity, seismic energy dissipation capacity, and ductility of assembled coupling beam structure decrease with the increase in end block thickness. Numerical simulation shows that increasing the area of equivalent steel bars will increase its yield load but will also reduce the seismic energy dissipation capacity and ductility. The thicker the shear wall thickness, the higher specimen’s bearing capacity, the stronger the seismic energy dissipation capacity, and the worse the ductility is.